La représentation des grands espaces nord-américains dans Capitaine Apache (Lécureux – Norma, 1975-1986) - Jean-Yves Puyo (Strenae)
This research suggests to study the series Captaine Apache, published in the columns of the weekly magazine Pif Gadget between 1975 and 1988. Western series in the "realistic" vein, like Jerry Spring (Jijé, 1954) or Blueberry (Giraud - Charlier, 1963), it narates the playful adventures of a young "mestizo", Apache on his mother's side and of Scottish "roots" on his father's, Okada, presented from the very first adventure by his authors (Norma in the drawings, Roger Lécureux in the scenario) as called to command, when he reaches adulthood, the Indian resistance to the episode of the conquest of the Wild West. Through the considerable publication figures of Pif Gadget, we defend the hypothesis that these series played a significant role on the representation carried by its many young readers (born in the 1960s and 1970s) of this North America’s wild spaces. In a recent research, devoted to the western comic series Blueberry and Mac Coy, we have shown that the landscapes reproduced by their drawers turn out to be the same as those conveyed by the films of the Hollywood Golden Age. However, according to the geographer Michel Foucher, these filmographic landscapes have little to do with those of the spaces in which the most important confrontations of the Indian Wars took place. So, would it be the same with the series Captaine Apache?